Correlation between motor function and health-related quality of life in early to mid-stage patients with Parkinson disease: a cross-sectional observational study - Ge, Ying; Zhao, Wowa; Zhang, Lu; Zhao, Xiaoyi; Shu, Xuan; Li, Jiawei; Liu, Ying (Frontiers in Aging Neuroscience, 2024)
Aim To investigate the correlation between motor function and health-related quality of life (HrQOL) in early to mid-stage patients with Parkinson disease (PwP). Methods This cross-sectional study recruited PwP from April 2020 to December 2023 at the outpatient clinic of Peking Union Medical College Hospital in Beijing, China. The motor symptoms were assessed using Movement Disorder Society–sponsored revision of the Unified Parkinson’s Disease Rating Scale (MDS-UPDRS) part 3. Balance function was evaluated using the Berg Balance Scale (BBS), and the risk of fall using Timed Up-and-Go test (TUG), and Five Times Sit-to-Stand test (FTSST). Freezing of gait questionnaire (FOGQ) was used to evaluate the severity of gait. The Intelligent Device for Energy Expenditure and Physical Activity (IDEEA) recorded gait cycle parameters, and the isokinetic dynamometer measured muscle strength. The Parkinson’s Disease Questionnaire-39 (PDQ-39) was used to measure HrQOL. All assessments were tested during the on state. Spearman correlation was conducted to evaluate the correlation between motor function and HrQOL. Results 243 patients with mean age of 69.33 years were enrolled. The PDQ-39 score was strongly correlated with FOG in H&Y stage III (r = 0.653, p < 0.001) and moderately correlated in H&Y stage I (r = 0.471, p < 0.001) and H&Y stage II (r = 0.386, p < 0.001). Furthermore, the FOG was strongly correlated with mobility domain at H&Y stage III (r = 0.694, p < 0.001) and moderately correlated at H&Y stage I (r = 0.431, p < 0.001) and H&Y stage II (r = 0.434, p < 0.001). All motor function scores were correlated with PDQ-39 scores at H&Y stage III (p < 0.05). Conclusion Motor function correlated with HrQOL in early to mid-stage PwP, and FOG was the main factor, especially affecting mobility, activities of daily life and communication. HrQOL in patients at different disease stages were variously affected by motor function, and HrQOL and multiple dimensions was significantly associated with motor function in patients at H&Y stage III.